Education Transformation in The Digital Era: The Innovative Role of The Cake Application in Improving English Speaking Skills - Suardana, I Gede Sentana (STKIP AGAMA HINDU SINGARAJA, 2024)
Education plays a crucial role in shaping human character and personality development. The Merdeka Belajar (Freedom of Learning) program underscores the significance of learning autonomy and innovation in education. This article investigates the impact of technology, specifically the Cake application, on enhancing English speaking skills within the classroom context. Using the Classroom Action Research (CAR) approach, this study examines the efficacy of the Cake app in improving English pronunciation skills among 9th-grade students at SMP N 3 Kubutambahan. Through four research cycles, the study demonstrates the Cake app's effectiveness in enhancing students' English-speaking abilities. Findings also support the app's utility in improving student speaking skills. In conclusion, teaching English pronunciation with the Cake app garnered positive feedback from students, indicating successful implementation of pronunciation instruction among 9th-grade students at SMP N 3 Kubutambahan.